Diversity of SCCmec Elements in Staphylococcus aureus as Observed in South-Eastern Germany - Monecke, Stefan (PLoS One, 2016)
SCCmec elements are very important mobile genetic elements in Staphylococci that carry beta-lactam resistance genes mecA/mecC, recombinase genes and a variety of accessory genes. Twelve main types and a couple of variants have yet been described. In addition, there are also other SCC elements harbouring other markers. In order to subtype strains of methicillin-resistant S. aureus (MRSA) based on variations within their SCCmec elements, 86 markers were selected from published SCC sequences for an assay based on multiplexed primer extension reactions followed by hybridisation to the specific probes. These included mecA/mecC, fusC, regulatory genes, recombinase genes, genes from ACME and heavy metal resistance loci as well as several genes of unknown function. Hybridisation patterns for published genome or SCC sequences were theoretically predicted. For validation of the microarray based assay and for stringent hybridisation protocol optimization, real hybridization experiments with fully sequenced reference strains were performed modifying protocols until yielded the results were in concordance to the theoretical predictions. Subsequently, 226 clinical isolates from two hospitals in the city of Dresden, Germany, were characterised in detail. Beside previously described types and subtypes, a wide variety of additional SCC types or subtypes and pseudoSCC elements were observed as well as numerous composite elements. Within the study collection, 61 different such elements have been identified. Since hybridisation cannot recognise the localisation of target genes, gene duplications or inversions, this is a rather conservative estimate. Interestingly, some widespread epidemic strains engulf distinct variants with different SCCmec subtypes. Notable examples are ST239-MRSA-III, CC5-, CC22-, CC30-, and CC45-MRSA-IV or CC398-MRSA-V. Conversely, identical SCC elements were observed in different strains with SCCmec IVa being spread among the highest number of Clonal Complexes. The proposed microarray can help to distinguish isolates that appear similar or identical by other typing methods and it can be used as high-throughput screening tool for the detection of putative new SCC types or variants that warrant further investigation and sequencing. The high degree of diversity of SCC elements even within so-called strains could be helpful for epidemiological typing. It also raises the question on scale and speed of the evolution of SCC elements.